2013
DOI: 10.2166/wst.2013.677
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Escherichia coli in rural household container waters

Abstract: Plastic containers in the range of 5-20 L are widely used - especially in rural African settings - to collect, transport and store water for domestic use, including drinking, bathing and hygiene. The pathogen content of the waters in these containers has not been adequately characterized as yet. This paper presents the primary findings of a synoptic survey of drinking water quality samples from these containers and involved collection of bacterial indicator and pathogenicity gene data. In total, 571 samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The negative impact of contaminated drinking water on human health has been documented in many studies [3,4,32,33]. Human and animal activities were observed to play a role in the contribution of E. coli to the environment including in river waters [34].…”
Section: Resultsmentioning
confidence: 99%
“…The negative impact of contaminated drinking water on human health has been documented in many studies [3,4,32,33]. Human and animal activities were observed to play a role in the contribution of E. coli to the environment including in river waters [34].…”
Section: Resultsmentioning
confidence: 99%
“…We chose to model the amount of fecal matter ingested by children from hands and water and not the dose of enteric pathogens ingested as would be standard in risk modeling approaches such as a quantitative microbial risk assessment . The reason we chose this approach is because there is a striking lack of data on enteric pathogen concentrations in household environments of low-income countries. The lack of data is due to the difficulty measuring low prevalence, low concentration targets in environment matrices, making the collection and processing of environmental samples for pathogen detection in low-resource settings technically difficult, expensive, and often logistically infeasible. Also, by analyzing fecal ingestion instead of pathogens, the model can estimate potential impacts of behavioral interventions on various fecal-oral transmitted diseases and health impacts for children in low-income countries, not just the specific pathogen(s) modeled and not just diarrheal disease (e.g., soil-transmitted helminths, environmental enteropathy, malnutrition, schistosomiasis, respiratory infection, and trachoma). , …”
Section: Methodsmentioning
confidence: 99%
“…Res. 7 (7) [5], there is no difference between E. coli in intestine, in environment, and the calculation of coliform individuals is valid. E. coli which spreading in environment had potential for contaminating household watersource and drinking water station.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Jagals et al [7] found that the seven genes of invasive and hemorrhagic E. coli strains in the waters. Container had a central role in supplying water to rural communities so further microbiological characterization in water is so much needed.…”
Section: Issn: 2320-5407mentioning
confidence: 99%